Effect of Elevated Temperature on Growth Parameters and Seed Set of Setaria pumila (Yellow Foxtail) and Amaranthus palmeri (Palmer amaranth) in Southern USA - Amarnadh Oleti; Amna Dar; Sanju Shrestha; Grishma Ojha; Te-Ming Tseng; Swati Shrestha (Agronomy, 2024)
The steady increase in temperature due to global warming can significantly impact weed growth. This study investigates the response of the yellow foxtail (Setaria pumila (Poir.) Roem. & Schult.) grass weed and the Palmer amaranth (Amaranthus palmeri S. Watson) broadleaf weed to increasing temperature conditions, simulating future climate conditions. Temperature treatments included growing these weeds in three temperature-controlled growth chambers: control or ambient conditions (15.5/12.8 °C day/night), moderately elevated temperatures (17.2/14.4 °C), and elevated temperatures (18.8/16.1 °C). Monthly adjustments in the growth chambers simulated the natural temperature rise observed from April to June in the Southern USA, aligning with the respective treatments. Different plant parameters recorded included days to emergence, number of tillers/leaves, chlorophyll content, days to first inflorescence, biomass, and seed set. One-way ANOVA indicated a significant temperature impact on all the parameters assessed (p < 0.05), except for biomass (for both weeds) and days to first inflorescence and yield (for Palmer amaranth (p > 0.05)). The average days to emergence were the lowest under elevated temperatures (8 days for yellow foxtail and 11 days for Palmer amaranth) when compared to that for the control (10 days for yellow foxtail and 19 days for Palmer amaranth). By week 5, yellow foxtail exhibited notably greater tiller numbers under elevated temperatures compared to that of the control; a similar trend was noticed regarding the number of Palmer amaranth leaves. The average chlorophyll content was the highest under elevated temperature conditions up to week 6 and began decreasing after that for both weeds. The average yield of yellow foxtail under elevated, moderately elevated, and control temperatures was 7.55, 2.69, and 0.88 g, respectively. Even though not significant, the yield of Palmer amaranth was higher under elevated temperature conditions as compared to that under the ambient condition. The biomass of both yellow foxtail and Palmer amaranth were not significantly impacted by temperature (p > 0.05). Our research shows that as temperatures rise, weeds exhibit more vigorous growth and show higher photosynthetic efficiency, which has important implications for how we manage weeds in agriculture. These findings suggest that under warmer conditions, weeds could display more vigorous vegetative growth, thus significantly impacting crop yields. As we face ongoing global warming, it is crucial to consider how temperatures influences weed growth when designing strategies to manage weeds effectively.